2020
DOI: 10.1021/acs.analchem.9b04699
|View full text |Cite|
|
Sign up to set email alerts
|

Enantioselective Separation Using Chiral Amino Acid Functionalized Polyfluorene Coated on Mesoporous Anodic Aluminum Oxide Membranes

Abstract: Homochiral mesoporous anodic aluminum oxide membranes (AAO) were prepared by coating protected chiral D/L aspartic acid appended polyfluorene in the pores. These chiral AAO membranes successfully demonstrated enantioselective recognition and separation of a range of amino acids from their aqueous racemic mixture by simple filtration. Enantioselective separation was achieved by selective adsorption of one enantiomer from the aqueous racemic mixture into the chiral pores of the AAO membrane leaving the filtrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…One enantiomer was absorbed within the chiral pores, and the other enantiomer was left in the filtrate. This study revealed that the modulation of polymer-coated membrane and pore size can effectively enhance the separation process [108]. Various other applications of AAO membranes for filtration purposes have been reported in the literature and are also given in Table 4 AAO based 3D microchannels 50 Microchannels for molecular separation [109] Two nano-porous AAO membranes sandwiched in between PDMS layers 30 80 Two AAO membranes sandwiched between PDMS for Exosomes Isolation [106] AAO membrane in micro hydraulic mechanical system 50 Vibro-active nano filter for filtration, separation, and transportation of particles, using standing surface acoustic waves (SSAW) [110] Optical gas sensing package covered with AAO membrane 40 Filtration interface to let air and other gases pass and prevent contaminations in forms of particles for an optical gas sensor [111] AAO tubular membrane 20 Potential application for hemodialysis [112] AAO membrane and polydimethylsiloxane (PDMS) microwells with through holes 25 Microwell-assisted filtration of algal solution [113] (Continued)…”
Section: Aao Membrane For Filtration 321 Applications Of Aao Membrane...mentioning
confidence: 81%
See 1 more Smart Citation
“…One enantiomer was absorbed within the chiral pores, and the other enantiomer was left in the filtrate. This study revealed that the modulation of polymer-coated membrane and pore size can effectively enhance the separation process [108]. Various other applications of AAO membranes for filtration purposes have been reported in the literature and are also given in Table 4 AAO based 3D microchannels 50 Microchannels for molecular separation [109] Two nano-porous AAO membranes sandwiched in between PDMS layers 30 80 Two AAO membranes sandwiched between PDMS for Exosomes Isolation [106] AAO membrane in micro hydraulic mechanical system 50 Vibro-active nano filter for filtration, separation, and transportation of particles, using standing surface acoustic waves (SSAW) [110] Optical gas sensing package covered with AAO membrane 40 Filtration interface to let air and other gases pass and prevent contaminations in forms of particles for an optical gas sensor [111] AAO tubular membrane 20 Potential application for hemodialysis [112] AAO membrane and polydimethylsiloxane (PDMS) microwells with through holes 25 Microwell-assisted filtration of algal solution [113] (Continued)…”
Section: Aao Membrane For Filtration 321 Applications Of Aao Membrane...mentioning
confidence: 81%
“…Two-layered AAO membrane structures have been used for effective dialysis and to sieve exosomes, potential biomarkers for the early detection of cancerous cells [106]. Functionalized AAO membranes for purification of contaminated water and enantioselective separation have also been reported in the literature [107,108]. Figs.…”
Section: Aao Membrane For Filtration 321 Applications Of Aao Membrane...mentioning
confidence: 99%
“…Amino acids, as the basic components of proteins, play a vital role in the life activities of organisms, while amino acids with different chiralities have completely different physiological effects. Therefore, it is of great significance for the separation of chiral amino acids and their derivatives. , In our work, enantiopure DPE (1 S ,2 S -(−)-1,2-diphenyl-1,2-ethanediamine) as a chiral spacer is introduced into the GCN interlayers through the coordination anchoring of copper ions (Cu 2+ ); hence, a chiral environment is created in the interlayer space to allow enantioselective permeation from racemate molecules. Herein, we used a GCN-Cu-DPE membrane 900 nm in thickness on a PES substrate to conduct isobaric enantioselective permeation tests for various chiral amino acid enantiomers with molecular weights ranging from 89 to 204 for 12 h (Figures S22–S25, Tables S5 and S6).…”
Section: Resultsmentioning
confidence: 99%
“…TH membrane materials are mainly classified as inorganic, organic, and composite materials. [ 35 ] Inorganic materials mainly include anodic aluminum oxide (AAO) [ 36–41 ] and silicon‐based materials (Silicon nitride, SiN, and SiO 2 , for example). [ 42–47 ] The pore sizes of these inorganic membranes are typically at the nanoscale, ranging from a few nanometers to several hundred nanometers, and involve biochemical sensing applications.…”
Section: Types Of M/n‐pmsmentioning
confidence: 99%